Delphine Demelas, Sur un air épique, sur un air lyrique : célébrer le bon connétable. Édition critique et commentaires du manuscrit 428 (306) de la bibliothèque municipale d’Aix-en-Provence contenant La Chanson de Bertrand du Guesclin de Cuvelier suivie de pièces lyriques - Delphine Demelas (Perspectives Médiévales)
The manuscript Aix-en-Provence, municipal library, 428 (306) contains two different texts. The first, La Chanson de Bertrand du Guesclin, is an epic poem telling the life of Bertrand du Guesclin (1320-1380), a Britain knight from a modest background who took part of the One Hundred Years War, and would become the constable of France. This biography has been written by a certain Cuvelier between 1380 and 1385, right after Bertrand’s death. The second is a set of seven lyric poems written in memory of Bertrand, three of which were written by Eustache Deschamps. The first text, historical, epic, biographical, and poetic at the same time, has a considerable importance in the literary production of the day as the last chanson de geste to be written in French. The poems celebrating the constable are fully in line with the lyric revival of the end of the 14th century. The three volumes of this edition provide the original text of the manuscript, descriptions of the other manuscripts, a literary review including a study of the context and new information about the author, a linguistic study, critical notes, a glossary, an index, a list of proverbs, and a bibliography.